Efficacy of foam sclerotherapy accompanied by near infrared light and duplex ultrasonography in treatment of symptomatic recurrent varicose veins: A retrospective cohort study - Kahraman, Nail; Demir, Deniz (Journal of Surgery and Medicine, 2019)
Aim: The recurrence of Great Saphenous Vein (GSV) and that of Small Saphenous Vein (SSV) is a common, costly and complex challenge which is related with technically insufficient surgery or insufficient endovenous ablation and neovascularization. The purpose of this study is to assess the efficacy and the reliability of the foam sclerotherapy with Near Infrared (NIR) Light and/or Duplex Ultrasonography (DUS) in the treatment of the symptomatic Recurrent Varicose Veins (RVV). Methods: One hundred sixty four patients (181 legs) who had been treated between April 2014 and May 2017 have been studied retrospectively. The demographic data of the patients, DUS findings, Clinical, Etiologic, Anatomic and Pathophysiologic (CEAP) classification, peri-operative data and follow-up examinations were recorded. Results: The mean age our patients were 44.79±12.57 and 76 of them were females. It was detected that RVV in 145 extremities were developed after the open surgery (GSV ligation, GSVstripping, SSV ligation and phlebectomy) and that RVV in 36 extremities were developed after endovenous ablation (Radiofrequency ablation, Laser ablation). The reflux pathologies which led to RVV were evaluated in four groups such as incompetent saphenofemoral junction (SFJ) ±neovascularization in 114 patients, reflux from incompetent perforator / reflux from pelvic vein in 17 patients, incompetent SFJ ±neovascularization in 15 patients and combined causes in 35 patients. The stages of the patients were detected as C2 for 24 patients, as C3 for 91 patients, as C4 for 45 patients, as C5 for 16 patients and C6 for five extremities. Total occlusion was developed occurred in 172 extremities in the sixth-month control following the treatment. No major complication was seen during the follow-up. Conclusions: Tactical and technical errors, the progression of the diseases, neovascularization may lead to RVV. The redo open surgery is more difficult compared to primary surgery. Besides, the neurovascular injury and the infection incidence of the redo surgery may be higher compared to primary surgery. Nowadays, open surgery, endovenous ablation, sclerotherapy, mechanochemical ablation (N-butyl-cyanoacrylate) may be performed in the treatment of the RVV. According to our experiences, we suggest that when foam sclerotherapy is applied in companion with NIR light and/or DUS it is a reliable, effective and cheaper treatment option that may be considered an alternative to other treatments in the convenient patients for the treatment of RVV.